Eksplorasi Hambatan-hambatan Siswa Dalam Memecahkan Masalah Program Linear di Sekolah Menengah Kejuruan - Andono, Joko; Nugroho, Purna Bayu; Handayani, Ratih (International Journal of Progressive Mathematics Education, 2022)
This study aims to identify the difficulties of class X students at SMK Muhammadiyah 1 Kotabumi in studying Mathematics on Linear Programming material. The type and approach in this research is a descriptive research type with a qualitative approach. The data collection techniques in this study were tests, observations, questionnaires, while data processing used the percentage formula P = f/n x 100%. From the results of the research it can be concluded that the difficulties of students in class X SMK Muhammadiyah Kotabumi in Linear Program material are the lack of understanding of students in understanding the concept of Linear Programming, often using the wrong formula and still confused in making a mathematical model, also the teacher's habits in learning mathematics in a way , just take notes on the blackboard, then students lack the desire to complete the sample questions given by the teacher. So that it can be concluded that the hypothesis is proven true that there are learning difficulties in mathematics in the Linear Program material for class X students of SMK Muhammadiyah 1 Kotabumi.   Penelitian ini bertujuan untuk mengidentifikasi kesulitan-kesulitan siswa kelas X SMK Muhammadiyah 1 Kotabumi dalam mempelajari mata pelajaran Matematika pada materi Program Linear.  Jenis dan pendekatan dalam penelitian ini adalah jenis penelitian deskriptif dengan pendekatan kualitatif. Adapun teknik pengumpulan data dalam penelitian ini adalah dengan tes, observasi, angket, sedangkan untuk pengolahan data mengunakan rumus persentase P = f/n x 100 %. Dari hasil penelitiaan di dapat kesimpulan bahwa kesulitan siswa dalam kelas X SMK Muhammadiyah Kotabumi dalam materi Program Linear adalah kurangnya pemahaman siswa dalam memahami konsep Program Linear, sering salah menggunakan rumus dan masih bingung dalam membuat suatu model matematika, juga kebiasaan guru dalam belajar matematika dengan cara, mencatat saja di papan tulis, kemudian siswa kurang keinginannya dalam menyelesaikan contoh soal yang diberikan oleh guru. Sehingga bisa diambil kesimpulan bahwa hipotesisnya terbukti benarbahwa adanya kesulitan belajar dalam pelajaran matematika pada materi Program Linear siswa kelas X SMK Muhammadiyah 1 Kotabumi.